Exosomal long non-coding RNA-LINC00839 promotes lung adenocarcinoma progression by activating NF-κB signaling pathway - Yue Sun; Fang Zhen; Hongyi Wang; Xiao Liang; Yaru Wang; Feiran Wang; Jing Hu (Annals of Medicine)
Background Lung adenocarcinoma is the most common type of lung cancer, accounting for approximately 40% of all lung cancer cases, and has the highest incidence among lung cancer subtypes. Recent studies have suggested that long non-coding RNAs (lncRNAs) play a crucial role in the initiation and progression of lung adenocarcinoma.Methods Based on integrative analysis through databases, we screened Long intergenic non-protein coding RNA 00839 (LINC00839) as one of the most highly upregulated lncRNAs in lung adenocarcinoma. In vitro and in vivo experiments demonstrated that LINC00839 promotes lung adenocarcinoma proliferation, migration, and invasion and that it is present in exosomes secreted by lung adenocarcinoma cells.Results In the cytoplasm, LINC00839 regulates the Toll-like receptor 4 (TLR4)/NF-κB signaling pathway by acting as a molecular sponge of miR-17-5p, thereby influencing the biological behavior of lung adenocarcinoma cells. LINC00839 binds to Polypyrimidine tract binding protein 1 (PTBP1) in the nucleus to regulate the nuclear translocation of NF-κB p65 molecules and, consequently, the transcription of downstream molecules.Conclusions Our study confirmed that LINC00839 promotes the biological progression of lung adenocarcinoma by performing dual roles in the cytoplasm and nucleus to co-regulate the NF-κB signaling pathway.